1983
DOI: 10.1007/bf00206272
|View full text |Cite
|
Sign up to set email alerts
|

The pineal organ of Raja clavata: Opsin immunoreactivity and ultrastructure

Abstract: The pineal organ of Raja clavata was studied by light and electron microscopy, including the immunocytochemical antiopsin reaction. The pineal organ of the ray consists of three portions: (i) a large proximal pineal, (ii) a long tube-like connecting stalk, and (iii) a short distal terminal enlargement. This latter end-vesicle lies in the deep connective tissue layers of the braincase. All portions of the pineal are composed of pinealocytes, intrinsic neurons, ependymal/glial cells, and bundles of nerve fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The presence of putative pinealopetal neurons in the dogfish and skate is in agreement with the ultrastructural finding, in the pineal parenchyma, of synaptic boutons that contain dense-cored vesicles and that are clearly different from pinealocyte terminals (Rüdeberg 1969;Vigh-Teichmann et al 1983). Putative pinealopetal cells have been found in the diencephalon and mesencephalon of sturgeon and the mesencephalon of larval lampreys after application of DiI to the pineal organ (Yáñez et al 1993;Yáñez and Anadón 1998).…”
Section: Pinealopetal Neuronssupporting
confidence: 67%
See 1 more Smart Citation
“…The presence of putative pinealopetal neurons in the dogfish and skate is in agreement with the ultrastructural finding, in the pineal parenchyma, of synaptic boutons that contain dense-cored vesicles and that are clearly different from pinealocyte terminals (Rüdeberg 1969;Vigh-Teichmann et al 1983). Putative pinealopetal cells have been found in the diencephalon and mesencephalon of sturgeon and the mesencephalon of larval lampreys after application of DiI to the pineal organ (Yáñez et al 1993;Yáñez and Anadón 1998).…”
Section: Pinealopetal Neuronssupporting
confidence: 67%
“…Studies of the pineal organ of elasmobranchs (sharks: Studnička 1905;Holmgren 1918;Altner 1965;Rüdeberg 1968Rüdeberg , 1969skates: Vigh-Teichmann et al 1983) have revealed up to five cell types in the pineal parenchyma: photoreceptors, glycogen-storing cells (a receptor cell descendant), supporting cells, cytosome-rich cells (supporting cell descendants), and ganglion cells. Following immunocytochemistry, the outer segments of the pinealocytes of the skate show a strong anti-opsin reaction (Vigh-Teichmann et al 1983). Pineal ganglion cells show acetylcholinesterase activity in a species of shark (Ueck 1979), and, in the dogfish, pineal photoreceptors have been shown to be choline-acetyltransferaseimmunoreactive (Anadón et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Ultrastructurally, the photoreceptor cells are endowed with outer segments that resemble the cones of the retina in the arrangement of their membrane disks (Hyla regilla: EAKIN,1961;EAKIN et al, 1961EAKIN et al, , 1963Rana esculenta, R. temporaria: OKSCHE andVON HARNACK, 1962, 1963;OKSCHE and VAUPEL-VON HARNACK, 1963 pipiens: KELLY and SMITH, 1964;ELDRED and NOLTE, 1981;Xenopus laevis: KORF et al, 1981). However, the antigenicity of the frog pineal photoreceptor has been found to be predominantly of the rod-type (VIGH-TEICHMANN et al, 1980a, 1983a.…”
Section: Discussionmentioning
confidence: 99%
“…22). The subependymal neuronal perikarya of some cartilagineous fishes send ciliated dendrites into the lumen of the pineal organ (Triakis scyllia: Ueck and Kobayashi, 1979;Raja clavata: Vigh and Vigh-Teichmann, 1989b;Vigh-Teichmann et al, 1983b;Vigh-Teichmann and Vigh, 1989). These nerve cells resemble bipolar neurons of the retina that form Landolt's clubs and have a receptory pole identical to that of hypothalamic CSF-contacting neurons (Fig.…”
mentioning
confidence: 99%